Dziedzictwo rosyjskiej szkoły formalnej. OPOJAZ i Moskiewskie Koło Lingwistyczne a współczesna filologia - Pilszczikow, Igor; Berkieta, Aleksandra (Tł.) (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
This article is devoted to the basic ideas of Russian formalism and their later development in the Russian scholarship from the 1960s to the present time. The traditional view which is focussed on the Society for the Study of Poetic Language (Obščestvo po izučeniju poètičeskogo jazyka — OPOJAZ) is corrected and supplemented by the synopsis of the achievements of the Moscow Linguistic Circle (Moskovskij lingvističeskij kružok — MLK). Special attention is paid to the works of Maksim Kenigsberg, Grigory Vinokur, Osip Brik and Boris Jarcho, as well as the use of linguistic, semiotic, and statistical methods in literary studies.
The heritage of the Russian formal school. OPOJAZ and the Moscow Linguistic Circle and the modern philology